2015
DOI: 10.1158/2159-8290.cd-15-0671
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer Metabolism: Breaking It Down to Build It Back Up

Abstract: How do cancer cells escape tightly controlled regulatory circuits that link their proliferation to extracellular nutrient cues? An emerging theme in cancer biology is the hijacking of normal stress response mechanisms to enable growth even when nutrients are limiting. Pancreatic ductal adenocarcinoma (PDA) is the quintessential aggressive malignancy that thrives in nutrient-poor, hypoxic environments. PDAs overcome these limitations through appropriation of unorthodox strategies for fuel source acquisition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
180
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(184 citation statements)
references
References 143 publications
4
180
0
Order By: Relevance
“…PDAC cells adapt to life under limited nutrient conditions by relying on scavenging pathways for growth; namely, macropinocytosis and autophagy Commisso et al 2013;Perera and Bardeesy 2015). Importantly, both of these pathways converge on the lysosome for breakdown of scavenged material, and recent studies have shown that the lysosomal compartment is greatly expanded in PDAC cells .…”
Section: Identifying Potential Responders To Autophagy Inhibition Inmentioning
confidence: 99%
“…PDAC cells adapt to life under limited nutrient conditions by relying on scavenging pathways for growth; namely, macropinocytosis and autophagy Commisso et al 2013;Perera and Bardeesy 2015). Importantly, both of these pathways converge on the lysosome for breakdown of scavenged material, and recent studies have shown that the lysosomal compartment is greatly expanded in PDAC cells .…”
Section: Identifying Potential Responders To Autophagy Inhibition Inmentioning
confidence: 99%
“…Metabolic reprogramming is one of the key events in pancreatic tumor biology which helps cancer cells to survive and grow under harsh microenvironment with depleted nutrient and oxygen level. [2][3][4] Several of the metabolic adaptations including increase in glucose uptake, enhanced glycolysis, increased flux of glycolysis intermediates into anabolic pathways, canonical and noncanonical glutamine metabolism and activation of recycling and scavenging processes support an increased demand for energy and biosynthesis by tumor cells and also maintain an optimal redox balance to support growth and progression. 3 Although critically important, metabolic adaptations are highly complex and context-dependent dynamic events, and the mechanisms of their regulation are not yet completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…This dismal outcome is mainly due to the lack of methods for early detection and to the fact that it develops early resistance against most forms of conventional cytotoxic therapy [1]. Important progress seen in the past years have, however, improved our understanding of the genetic basis and the biological pathways of this disease and opened up new therapeutic options for targeting tumor metabolism [2,3]. Yet a better understanding of how metabolic pathways are regulated in cancer is necessary to devise more effective therapies.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported to function as a putative tumor suppressor in several types of cancer [7][8][9]. Because changes in metabolism are regarded to be critical during malignant transformation [3,[10][11][12], we studied the levels of FOXO1 throughout the development of human PDAC.…”
Section: Introductionmentioning
confidence: 99%